Desenvolvimento de revestimentos siloxano-PMMA reforçados por nanotubos de carbono, óxido de grafite e óxido de grafite reduzido para aplicações anticorrosivas - Harb, Samarah Vargas [UNESP] (2015)
Anticorrosive coatings siloxane-PMMA hybrid reinforced by carbon nanotubes, graphite oxide and reduced graphite oxide were synthesized using the sol-gel process. Initially, the carbon nanostructures were characterized by X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The siloxane-PMMA hybrids were prepared from the radical polymerization of methyl methacrylate monomer (MMA) with 3-methacryloxypropyltrimethoxysilane (MPTS) using the thermal initiator benzoyl peroxide (BPO), followed by hydrolysis and condensation of tetraethoxysilane (TEOS) acid catalyzed. The single-walled carbon nanotubes were dispersed using the surfactant sodium dodecyl sulfate (SDS) and palmitic acid, and then they were added in a molar concentration of C/Si = 0.018%. Graphite oxide (GO) was added both in powder form and in the form of dispersed solution in water/ethanol at 0.01%, 0.05%, 0.1% and 0.5% concentrations (molar ratio C/Si). The sample containing 0.05% of dispersed graphite oxide solution was used to study the reduction of graphite oxide using the ascorbic acid reducing agent in three concentrations (molar ratio of ascorbic acid/GO: 0.24, 2.4 and 24). The structural and morphological analysis of the hybrids were performed by 29Si nuclear magnetic resonance (NMR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, atomic force microscopy (AFM) and wettability measurements. Thermogravimetric analysis was performed for analysis of thermal properties, and hardness measurements and microscratch for analysis of mechanical properties of the hybrids. Electrochemical impedance spectroscopy (EIS) was used to evaluate the coatings anticorrosion efficiency after long-term exposure in saline environment. The presence of low concentrations of graphite oxide and carbon nanotubes led to increased thermal stability, hardness, scratch...